2021
DOI: 10.3389/fphar.2021.736829
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Carveol Prevents Gastric Ulcers via Cytoprotective, Antioxidant, Antisecretory and Immunoregulatory Mechanisms in Animal Models

Abstract: Background: (-)-Carveol (p-Mentha-6,8-dien-2-ol) is a monocyclic monoterpenic alcohol, present in essential oils of plant species such as Cymbopogon giganteus, Illicium pachyphyllum and in spices such as Carum carvi (cumin). Pharmacological studies report its antitumor, antimicrobial, neuroprotective, vasorelaxant, antioxidant and anti-inflammatory activity.Hypothesis/Purpose: The objective of this study was to evaluate the acute non-clinical oral toxicity, gastroprotective activity of monoterpene (-)-Carveol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…Next, the abovementioned ethanol-induced gastric ulcer mouse model was established. Mice were pretreated with the blocking agents N-nitro-L-arginine methyl ester (L-NAME), N-ethylmaleimide (NEM), glibenclamide, and indomethacin before the ethanol gavage [ 25 ]. Each blocking agent corresponded to 2 groups of mice, one of which was the FPH gavage group and the other was the vehicle gavage group, for a total of 8 groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the abovementioned ethanol-induced gastric ulcer mouse model was established. Mice were pretreated with the blocking agents N-nitro-L-arginine methyl ester (L-NAME), N-ethylmaleimide (NEM), glibenclamide, and indomethacin before the ethanol gavage [ 25 ]. Each blocking agent corresponded to 2 groups of mice, one of which was the FPH gavage group and the other was the vehicle gavage group, for a total of 8 groups.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the involvement of KATP channels in the gastroprotection of FPH, mice were pretreated with glibenclamide (5 mg/kg, i.p.) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…155 Evaluation the acute non-clinical oral toxicity of carveol shows that LD 50 is equal to or greater than 2500 mg kg −1 . 16 The LD 50 of orally administered dihydrocarvone, dihydrocarveol and dihydrocarvyl acetate in rat is all greater than 5 g kg −1 . 152–154 A summary of the toxicological information of spearmint aromatic molecules is presented in Table 4.…”
Section: Side Effects and Toxicitymentioning
confidence: 98%
“…The authors concluded that the gastroprotective activity of carveol may be related to antisecretory, cytoprotective, antioxidant and immunomodulatory mechanisms. 16…”
Section: Biological Properties Of Spearmint Aromatic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation